(untitled) (Maharaja Surajmal Institute Law Journal, 2024)
The current century is the era of science and technology. Over the past few years, there have been numerous mechanical advancements. The development of information technology gave rise to the cyberspace, where internet connectivity allows users to access information and store data, among other things. The common man now has access to the internet, which is improving their quality of life. The most recent trend in information and communication technologies is similar to the fact that no coin has only one side. Cybercrimes were created when some individuals with criminal mindsets began using the internet for their illicit activities. Cybercrime and the exploitation of women are both continuously rising due to new technology. This article focusses on the new challenges surrounding cybercrimes against women in India and the factors contributing to their rise. In this article, suggestions have been provided by the authors which are helpful in combating cybercrimes.